Partisipasi Masyarakat Lokal dalam Pengembangan Kawasan Pariwisata Candidasa - Adikampana, I Made; Kerti Pujani, Luh Putu; Nugroho, Saptono (Jurnal Kajian Bali (Journal of Bali Studies); Vol 8 No 1 (2018): MODAL BUDAYA PARIWISATA BALIDO - 10.24843/JKB.2018.v08.i01.p04, 2018)
This article examines the local community participation in the Candidasa tourism area, Karangasem, Bali. The objectives are to identify the capital exchange practice of local communities with the tourism industry and then determine the type of local communities’ participation in the development of Candidasa tourism area. The community based tourism approach adopted to understand the phenomenon of local community participation. Based on observations and interviews can be addressed that the communities surrounding the Candidasa relatively have an exhaustive capital. However, the comprehensiveness of such capital is not accompanied by the proper capital exchange strategies by indigenous village institution as a representation of local communities. The local communities only get relief materials from tourism as a result of the capital exchange. Accordance with the practice of capital exchange, it can be said that this type of local community participation is included in the participation for material incentives. This type of community participation is still relatively limited, so it necessary to improve the their involvement into tourism development in Candidasa.